2017
DOI: 10.1016/j.optlaseng.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of multi-scale periodic surface structures on Ti-6Al-4V by direct laser writing and direct laser interference patterning for modified wettability applications

Abstract: In this work, hierarchical surface patterns fabricated on Ti-6Al-4V alloy combining two laser micro-machining techniques are presented. The used technologies are based on nanosecond Direct Laser Writing and picosecond Direct Laser Interference Patterning. Squared shape micro-cells with different hatch distances were produced by Direct Laser Writing with depths values in the micro-scale, forming a well-defined closed packet. Subsequently, cross-like periodic patterns were fabricated by means of Direct Laser Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…Both surfaces have pillars with an average depth at the maxima–maxima positions of 1.8 ± 0.25 and 3.0 ± 0.23 µm, correspondingly. As reported for Ti64 surfaces treated with ps‐DLIP, [ 38 ] the laser‐treated samples show additional surface features, which can be identified as low spatial frequency LIPSS (LSFL) with a spatial period of ≈400 nm. High spatial frequency LIPSS (HSFL) can be observed in perpendicular direction to the LSFL (inset in Figure 1b).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Both surfaces have pillars with an average depth at the maxima–maxima positions of 1.8 ± 0.25 and 3.0 ± 0.23 µm, correspondingly. As reported for Ti64 surfaces treated with ps‐DLIP, [ 38 ] the laser‐treated samples show additional surface features, which can be identified as low spatial frequency LIPSS (LSFL) with a spatial period of ≈400 nm. High spatial frequency LIPSS (HSFL) can be observed in perpendicular direction to the LSFL (inset in Figure 1b).…”
Section: Resultsmentioning
confidence: 63%
“…Different laser processes and pulse durations have been used to tune the surface wettability of metals by generating hierarchically structured superhydrophobic surfaces. [ 35–38 ] Many of these works suggest that such surfaces can be also used for icephobic applications. [ 39–41 ] In a research previously published, it was shown that Ti6Al4V (Ti64) offers a robust substrate for the laser‐generated features compared to Aluminum Alloy 2024 (AA2024), since these features providing the support for the Cassie–Baxter state remain unchanged on Ti64 after 16 icing/deicing cycles, while are partially destroyed on the AA2024.…”
Section: Introductionmentioning
confidence: 99%
“…electrodeposition step was used, which led to the deposition of spherical nickel droplets on the tips of the micro-textures as shown in Figure 4 [46]. Finally, an innovative method to create multi-scale surface textures is to combine two different laser processes, namely DLW and DLIP [76,77]. Thereby, the bigger surface textures are created by DLW and the smaller textures by DLIP.…”
Section: Multi-step Processesmentioning
confidence: 99%
“…Ahmmed and Kietzig used a femtosecond Ti:sapphire laser system with a wavelength of 800 nm and a pulse duration <85 fs to fabricate multi-scale textures on copper [81]. The laser inscribed primary pattern demonstrated a width of 14-80 µm and a depth of 60-130 µm whereas Finally, an innovative method to create multi-scale surface textures is to combine two different laser processes, namely DLW and DLIP [76,77]. Thereby, the bigger surface textures are created by DLW and the smaller textures by DLIP.…”
Section: Single-step Processesmentioning
confidence: 99%
“…The combination of HL and micropatterning methods, such as photolithography and direct laser writing, [129][130][131][132] can further provide multiscale structures having micro-and nanostructural features. The integration of HL-featured 3D nanostructures into microfluidic channels has produced optofluidic sensing platforms that embed optical sensing units, 3D passive mixers, and filters.…”
Section: Discussionmentioning
confidence: 99%